Evolution of the Polarizing Effect of MoS2 - Sathiyan, S.; Ahmad, Harith; Chong, W.Y.; Lee, S.H.; Sivabalan, S. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
We have explored the polarization behavior of MoS2 at three different wavelengths using a polymer-based waveguide. The MoS2-coated waveguide has been fabricated based on the drop casting method. The maximum polarization extinction ratio of 12.6 dB that is achieved at 980 nm is considered to be the highest, to the best of our knowledge, for the MoS2-based waveguide polarizer. It exhibits transverse electric (TE) pass characteristics in the visible wavelength region. The mode field confinement has been computed based on the finite-element method (FEM). Both numerical and experimental results are in very good agreement. These results demonstrate that the few-layer MoS2 can be considered as a complementary material for graphene-based polarizers.